Conceptual composting awareness model in Malaysian public university: A case study of Green Team IIUM - Hashim, Khairusy Syakirin Has-Yun; Mohamad, Abdul Hakim; Mohamed Shah Redza, Haneesa Zahidah (2011)
Waste issues have been discussed in many countries. Reports and discussion papers have been written in developed, developing and third world countries, which show that waste management is a common issue and problem globally. One of the solutions is by implementing the Waste Management Hierarchy. The real problem with the waste management is the composition of type of waste, which can be divided into two groups; wet waste (from kitchen waste) and dry waste. Composting is one of the possible solutions. But 3Rs (Reduce, Reuse and Recycle) are always being referred to solve the dry waste problem. Composting is always being left out from the 3Rs initiatives. Thus, the aim of this paper is to explore the Composting initiatives. The waste management awareness programme should include Composting as a possible initiative to reduce waste from entering landfills. Case study approaches has been conducted in the International Islamic University Malaysia. It is also the aim of this paper to suggest methods in creating awareness among students in universities by developing a Conceptual Composting Awareness Model (CCAM).